The Position And Position Of Al Quran As Islamic Law Sources - Kama Robbayani (Proceeding International Seminar of Islamic Studies, 2019)
Al Quran has a very high position of all Islamic teachings. Al Quran as the main and first source so that all muslims make Al Quran as a guide to life. This is the subject of Islamic teachings so that everything must be sourced or based on it. This becomes the base and the return of all things. It also becomes the center where something flows. . Therefore, as a good and perfect source, let it have a dynamic, true and absolute natere. Al-Quran is used as a basis for values for muslim in determining the law of an action, showing and guiding it on the path to its goals and explaining the nature of human life in relation to each other, the environment and with god. The scholars of ushul fiqh stipulate that the al-quran as a source of Islamic law has explained the laws contained therein by : the first, Detailed explanation (Juz’i) of some of the laws they contain, such as those relating to matters of faith, inheritance law, etc. The second, Al-quran explanation of most of these laws is global (Kulli), general and absolute, as in the matter of prayer and zakat. So it is very clear that the position of Al-Quran is as the main source of Islamic law that can be used as a way of life and guidance for mankind. There is no doubt whatsoever to him. And if that person holds fast to Al-Quran, the he will not be lost forever.